C-reactive protein velocity discriminates between acute viral and bacterial infections in patients who present with relatively low CRP concentrations - Daniel Bernstein (BMC, 2021)
Abstract Background To assess the utility of C-reactive protein (CRP) velocity to discriminate between patients with acute viral and bacterial infections who presented with relatively low CRP concentrations and were suspected of having a bacterial infection. Methods We analyzed a retrospective cohort of patients with acute infections who presented to the emergency department (ED) with a relatively low first CRP measurement (CRP1) ≤ 31.9 mg/L and received antibiotics shortly after. We then calculated C-reactive protein velocity (CRPv), milligram per liter per hour, for each patient based on CRP1 and the second CRP value (CRP2) measured within the first 24 h since admission. Finally, we compared CRPv between patients with bacterial and viral infections. Results We have presently analyzed 74 patients with acute bacterial infections and 62 patients with acute viral infections at the mean age of 80 and 66 years respectively, 68 male and 68 female. CRP1 did not differ between both groups of patients (16.2 ± 8.6 and 14.8 ± 8.5 for patients with viral and bacterial infections respectively, p value = 0.336). However, the CRP2 was significantly different between the groups (30.2 ± 21.9 and 75.6 ± 51.3 for patients with viral and bacterial infections respectively, p-value < 0.001) and especially the CRPv was much higher in patients with acute bacterial infections compared to patients with acute viral infections (0.9 ± 1.2 and 4.4 ± 2.7 respectively, p-value < 0.001). Conclusion CRPv and CRP2 are useful biomarkers that can discriminate significantly between patients who present with acute bacterial and viral infections, and relatively low CRP concentration upon admission who were suspected of having a bacterial infection.